Controlling cancer through the autotaxin–lysophosphatidic acid receptor axis. (19th January 2012) - Gotoh, Mari; Fujiwara, Yuko; Yue, Junming; Liu, Jianxiong; Lee, SueChin; Fells, James; Uchiyama, Ayako; Murakami-Murofushi, Kimiko; Kennel, Stephen; Wall, Jonathan; Patil, Renukadevi; Gupte, Renuka; et al.
Abstract : LPA (lysophosphatidic acid, 1-acyl-2-hydroxy- sn -glycero-3-phosphate), is a growth factor-like lipid mediator that regulates many cellular functions, many of which are unique to malignantly transformed cells. The simple chemical structure of LPA and its profound effects in cancer cells has attracted the attention of the cancer therapeutics field and drives the development of therapeutics based on the LPA scaffold. In biological fluids, LPA is generated by ATX (autotaxin), a lysophospholipase D that cleaves the choline/serine headgroup from lysophosphatidylcholine and lysophosphatidylserine to generate LPA. In the present article, we review some of the key findings that make the ATX–LPA signalling axis an emerging target for cancer therapy.